2013
DOI: 10.1089/jmf.2012.0131
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Treatment of Tart Cherry Extract and Essential Fatty Acids Reduces Cognitive Impairments and Inflammation in the mu-p75 Saporin-Induced Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects more than five million Americans and is characterized by a progressive loss of memory, loss of cholinergic neurons in the basal forebrain, formation of amyloid plaques and neurofibrillary tangles, and an increase in oxidative stress. Recent studies indicate that dietary supplements of antioxidants and omega-3 and omega-6 fatty acids may reduce the cognitive deficits in AD patients. The current study tested a combinatorial treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In various rat models, we reported that tart cherry fruit intake reduces blood lipids and inflammation and alters phenotypes of metabolic syndrome (Seymour et al, 2008;Seymour et al, 2009). Tart cherry also affects activity of PPARs in various tissues and various gene transcripts related to inflammation (Matchynski et al, 2013;Seymour et al, 2009;Zhou, Nair, & Claycombe, 2012). Phytochemicals in tart cherry fruits may be directly cytoprotective by altering gene transcription and translation, thereby improving resistance to oxidative and inflammatory stressors.…”
Section: Introductionmentioning
confidence: 99%
“…In various rat models, we reported that tart cherry fruit intake reduces blood lipids and inflammation and alters phenotypes of metabolic syndrome (Seymour et al, 2008;Seymour et al, 2009). Tart cherry also affects activity of PPARs in various tissues and various gene transcripts related to inflammation (Matchynski et al, 2013;Seymour et al, 2009;Zhou, Nair, & Claycombe, 2012). Phytochemicals in tart cherry fruits may be directly cytoprotective by altering gene transcription and translation, thereby improving resistance to oxidative and inflammatory stressors.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly so in adipose tissue; animals prone to obesity, insulin resistance and hyperlipidemia; and older adults with compromised resistance to oxidative stress. However, the sample sizes studied are very small and the authors did not provide evidence of sufficient statistical power to detect a true difference between placebo and treatment groups [10][11][12][13][14].…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…Anthocyanin intake in animals may contribute to improvements in certain chronic diseases associated with aging, such as hyperlipidemia, obesity, atherosclerosis, and Alzheimer's [10][11][12]. Matchynski et al found that a tart cherry extract combined with a fish and emu oil supplement lessened induced cognitive deficits in an Alzheimer's mouse model.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations